2016
DOI: 10.4103/2008-322x.188397
|View full text |Cite
|
Sign up to set email alerts
|

Role of fine needle aspiration cytology as a diagnostic tool in orbital and adnexal lesions

Abstract: Purpose:To evaluate the role of fine needle aspiration (FNAC) as a diagnostic tool in cases of orbital and ocular adnexal masses. Cytological findings were correlated with histopathological diagnosis wherever possible.Methods:FNAC was performed in 29 patients of different age groups presenting with orbital and ocular adnexal masses. Patients were evaluated clinically and investigated by non-invasive techniques before fine needle aspiration of the masses. Smears were analyzed by a cytologist in all cases. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…[21] In their series, it was not indicated whether the size, location, and the radiologic appearance of the lesions in terms of being focal or diffuse might have any effect on the rate of insufficient aspirates or the diagnostic accuracy of FNAC. Furthermore, similar to other FNAC-based studies, this study had limitations regarding being non-randomized and retrospective.…”
mentioning
confidence: 99%
“…[21] In their series, it was not indicated whether the size, location, and the radiologic appearance of the lesions in terms of being focal or diffuse might have any effect on the rate of insufficient aspirates or the diagnostic accuracy of FNAC. Furthermore, similar to other FNAC-based studies, this study had limitations regarding being non-randomized and retrospective.…”
mentioning
confidence: 99%
“…For cases for which both cytology and histopathology results were available, the rate of disagreement between the two modalities was surprisingly high but similar to that reported in the physician‐based literature. In people, fine needle aspirate for cytology of orbital lesions is nondiagnostic in 10%‐30% of cases and discordant with later histopathology in 10%‐31% of cases, while in our patient population 15% of cytology samples were nondiagnostic and 17% were overturned by later histopathology . No specific causative factors could be identified for cases in which cytology samples were considered nondiagnostic or were initially characterized as representative of an inflammatory rather than neoplastic process.…”
Section: Discussionmentioning
confidence: 59%
“…In people, fine needle aspirate for cytology of orbital lesions is nondiagnostic in 10%-30% of cases and discordant with later histopathology in 10%-31% of cases, while in our patient population 15% of cytology samples were nondiagnostic and 17% were overturned by later histopathology. [22][23][24][25][26] No specific causative factors could be identified for cases in which cytology samples were considered nondiagnostic or were initially characterized as representative of an inflammatory rather than neoplastic process. Of the 11 samples in these categories, 10 came from dogs who had undergone a CT and eight were obtained using ultrasound guidance, suggesting that failure to sample the lesion of interest was unlikely to be the reason for discordance.…”
Section: Discussionmentioning
confidence: 99%
“…Other diagnoses sharing comparable clinical features include inflammation, infections, medication effects, autoimmune disorders, ischemia, and other neoplasms. 5,8,10 One reliable and relatively safe preliminary diagnostic tool before attempting any invasive procedure is FNAB of the optic nerve head, discussed by Khan et al 11 Although not reported for the diagnosis of leukemic infiltration, FNAB has been used to diagnose other ophthalmologic issues such as optic disk melanocytoma. 12 In our case, cytopathology following FNAB revealed rare atypical cells, further adding to the suspicion of ALL recurrence.…”
Section: Isolated Optic Nerve Leukemic Relapse Diagnosed Via Fine Neementioning
confidence: 99%
“…13 FNAB is known to give a cellular yield in 89% of patients and the technique is safe with respect to preserving vision; the most common complication is self-resolving intraocular hemorrhage. 11 The biopsy is performed with a 25 or 27 gauge needle and hence the diagnostic yield is often low with only a few cells obtained to diagnose the disease. In reported literature, the concordance rate between FNAB and subsequent histopathology in 90%.…”
Section: Isolated Optic Nerve Leukemic Relapse Diagnosed Via Fine Neementioning
confidence: 99%